Pūrwa Bhūmi Kamulan (Kajian Teks: Konsep Brahma Tattwa) - Ida Bagus Putu Adnyana (Purwadita : Jurnal Agama dan Budaya, 2022)
God is an object of abstraction that is difficult to understand. However, God can be understood through several methods in the science of religion. Efforts to learn and understand God are widely discussed in Hindu religious studies. One of the most widely used studies is the Brahma Tattwa study. Brahma Tattwa is a study to learn and understand God through efforts to analyze sacred literature. Holistically, the researcher used a qualitative approach in carrying out this research. The primary source is Pūrwa Bhūmi Kamulan's papyrus which has been converted into Old Javanese text and its Indonesian translation. Based on the results of the researcher's analysis, Prwa Bhūmi Kamulan's lontar emphasizes the theological aspect of God in his personification as Bhatāra Guru and Bhatārī Umā who created the world. As the name implies, namely Pūrwa Bhūmi Kamulan, this lontar does discuss more about the beginning or the beginning of the world/earth.  Keywords: Brahma Tattwa, Pūrwa Bhūmi Kamulan.